Teachers' and students' sex relationship to students' performance and students' rating of teachers' personality characteristics. - Gayapa, Maria Daisy Grace (2000)
This study sought to find out the relationship of teachers' and students' sex to students' performance and students' rating of teachers' personality characteristics. The personality characteristics include physical attractiveness, humor, gestures, nonverbal expressions, dominance, grammar and discipline. There were eighty (80) respondents composed of forty (40) males and forty (40) females. They were UPV students officially enrolled in Com. II during the Second Semester AY 1999-2000. They were selected through stratified sampling. The study utilized the correlation research design. The Pearson Product Moment Correlation (r) was used to analyze result. The result of this study was non-significant revealing those teachers' sex and students' sex were not correlated to students' performance and students' rating of their teachers' personality characteristics. Thus, the two hypotheses: 1) Students with the same sex teachers tend to perfrom better and 2) Students with the same sex teacher tend to rate their teachers higher were rejected. Therefore, students may perform better and rate their teachers higher even if they do not have the same sex as their teacher.